Local Protests, Global Movements : Capital, Community, and State in San Francisco - Beitel, Karl (Book collections on Project MUSE., 2013)
A history of the antigentrification and housing rights movement in San Francisco, Local Protests, Global Movements examines the ability of local urban movements to engage in meaningful contestation with private real estate capital and area governmental leaders in the era of urban neoliberalism. Using San Francisco as an illuminating case study, Beitel analyzes the innovative ways urban social movements have organized around issues regarding land use, housing, urban ecology, and health care on the local level to understand the changing nature of protest formation around the world. Reconciling the passing of New Left Ideals and the emergence of mobilization on a global scale, he assesses the limits of contemporary urban movements as conduits for advancing a radical political program. Beitel argues these limits reflect recurrent problems of internal fragmentation, and the manner in which liberal democratic institutions structure processes of political participation and interest representation.